STANDARISASI RESEP SALA LAUAK DI KANAGARIAN ULAKAN KABUPATEN PADANG PARIAMAN - Wahyuni, Helva; Baidar, Baidar; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2015)
The background of this study because of the lack of standardization of recipes sala lauak. This study aims to find a standard recipe sala lauak, and quality lauak sala. This research is a descriptive qualitative study using the method mix (Mixed Method). This research was conducted in Kanagarian Ulakan and Tata boga Workshop FT UNP. There are two sources of data: qualitative data sources for society and source of quantitative data that is obtained from the 15 panelists. Qualitative data collection techniques are observation guides, interview guides and camera for documentation and quantitative data collection techniques are organoleptic test questionnaire format. Qualitative data analysis techniques using three grooves activity: data reduction, data presentation, draw conclusions and quantitative data analysis techniques using the formula (M x = Σ x / N). Based on the test results organopleptik sala lauak standard recipe that has been converted with 4 repetitions found the quality of the sala lauak is the shape (round with a diameter of 3 cm), color (golden yellow), aroma (aromadaun turmeric and aroma of salted fish), skin texture ( hard), the contents texture (soft), volume (hollow), and taste (savory and tasted anchovies).        Keywords: Standardization Recipes Sala LauakThe background of this study because of the lack of standardization of recipes sala lauak. This study aims to find a standard recipe sala lauak, and quality lauak sala. This research is a descriptive qualitative study using the method mix (Mixed Method). This research was conducted in Kanagarian Ulakan and Tata boga Workshop FT UNP. There are two sources of data: qualitative data sources for society and source of quantitative data that is obtained from the 15 panelists. Qualitative data collection techniques are observation guides, interview guides and camera for documentation and quantitative data collection techniques are organoleptic test questionnaire format. Qualitative data analysis techniques using three grooves activity: data reduction, data presentation, draw conclusions and quantitative data analysis techniques using the formula (M x = Σ x / N). Based on the test results organopleptik sala lauak standard recipe that has been converted with 4 repetitions found the quality of the sala lauak is the shape (round with a diameter of 3 cm), color (golden yellow), aroma (aromadaun turmeric and aroma of salted fish), skin texture ( hard), the contents texture (soft), volume (hollow), and taste (savory and tasted anchovies).        Keywords: Standardization Recipes Sala Lauak